Nursing Care For Patients With Respiratory System Problems Of Pleural Effusion In The Bougenvile Room Andi Makassau Pare-Pare Hospital - Wahyuni, Ria; Aini, Dwi Nur; Noor, Mohammad Arifin; Rasimin, Rosmini; Bubun, Juhelnita; Dunggio, Abdul Rivai Saleh; Mahoklory, Serly Sani (International Journal of Health Sciences, 2025)
Pleural effusion is the accumulation of fluid in the pleural space, a primary disease process is rare but usually occurs secondary to other diseases. Effusion can be a clear fluid, which may be a transudate, exudate or may be blood or pus. The purpose of the study is to carry out nursing care for clients experiencing pleural effusion at Andi Makkasau Pare-Pare Regional Hospital. The research method used is the case study research method, which is a study of humans (can be a group, organization or individual), events, backgrounds in depth, the purpose of the study is to obtain an in-depth picture of a case being studied, data collection is obtained from interviews, observations, and documentation. Based on the results of the assessment, the following nursing diagnoses can be formulated: Chest pain related to biological factors (especially tissue) and physical factors. Ineffective breathing patterns related to decreased lung expansion secondary to fluid accumulation in the pleural cavity.